Prevalence of Dry Eye After Cataract Surgery in Patients Visiting Layton Rahatulla Benevolent Trust (LRBT) Township, Lahore - Sultan, Ushna; Iqbal, Kashif; Anwar, Ahmed; Arif, Aqsa (Biological and Clinical Sciences Research Journal, 2025)
Dry eye disease (DED) is a common issue following cataract surgery, caused by factors such as surgical trauma and postoperative medications. In Pakistan, there is limited data on the prevalence of postoperative DED and its risk factors. Objective: To determine the frequency of dry eye disease after cataract surgery and to evaluate its association with demographic and clinical factors among patients undergoing phacoemulsification. Methods: A prospective descriptive observational study was conducted at Layton Rahmatulla Benevolent Trust (LRBT) Free Eye and Cancer Hospital, Township Lahore, from January to June 2025. A total of 221 patients aged 40–80 years undergoing phacoemulsification with posterior chamber intraocular lens implantation were enrolled using non-probability consecutive sampling. Patients with previous ocular surgery, ocular surface disorders, corneal pathology, or systemic connective tissue diseases were excluded. Baseline demographic and clinical data were recorded. Dry eye disease was evaluated using tear film breakup time (TBUT) and Schirmer test without anesthesia before surgery and during follow-up at one week, one month, and three months postoperatively. A TBUT value <10 seconds or Schirmer test value <10 mm was considered indicative of dry eye disease. Data were analyzed using SPSS version 25. Quantitative variables were summarized as mean ± standard deviation, while categorical variables were presented as frequencies and percentages. Stratification was performed by age, gender, and diabetic status, and the Chi-square test was used to determine statistical associations with a significance level of p ≤0.05. Results: The study included 221 patients with a mean age of 59.8 ± 9.6 years. Male patients comprised 55.7% of the cohort, while 44.3% were female. Diabetes mellitus was present in 38.9% of participants. Dry eye disease developed in 63 patients, yielding an overall prevalence of 28.5% three months after cataract surgery. Older age was significantly associated with postoperative dry eye (p=0.03), with the highest frequency observed in the 61–70 year age group. Diabetic patients demonstrated a significantly higher prevalence of dry eye compared with non-diabetic patients (37.2% vs. 23.0%, p=0.02). Gender did not show a statistically significant association with dry eye occurrence (p=0.28). Tear film parameters showed a marked early postoperative decline, with mean TBUT decreasing from 13.4 ± 2.7 seconds preoperatively to 9.6 ± 2.9 seconds at one week, followed by partial recovery to 11.8 ± 2.6 seconds at three months. Similarly, mean Schirmer test values decreased from 17.2 ± 3.5 mm preoperatively to 11.4 ± 3.2 mm at one week and improved to 14.9 ± 3.0 mm by three months (p<0.001). Conclusion: Dry eye disease is a common postoperative complication following cataract surgery, affecting nearly one-third of patients in this cohort. Advancing age and diabetes mellitus appear to be significant risk factors for its development. These findings suggest that routine postoperative screening for dry eye and early initiation of ocular surface management may improve visual comfort and patient satisfaction after cataract surgery.